2015
DOI: 10.1016/j.jpedsurg.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Th-17 cells infiltrate the liver in human biliary atresia and are related to surgical outcome

Abstract: Background: Biliary atresia (BA), a cholangiopathy of unknown aetiology affecting infants, is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 44 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…Of note, abundance of periductal IL‐17A + cells is associated with periportal infiltration of CD68 + iMΦ, and these portal IL‐17A + cells persist in the liver of patients with progressive disease. An increased number of periductal IL‐17A + cells was linked to worse surgical outcome of KPE in Europe, and elevated plasma levels of IL‐17A‐associated cytokines were determined in an Asian cohort of infants with BA . Whether infiltration of the liver with Th17 lymphocytes and CD68 + iMΦ at the time of diagnosis is linked to progressive intrahepatic bile duct injury following KPE in North America will require further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, abundance of periductal IL‐17A + cells is associated with periportal infiltration of CD68 + iMΦ, and these portal IL‐17A + cells persist in the liver of patients with progressive disease. An increased number of periductal IL‐17A + cells was linked to worse surgical outcome of KPE in Europe, and elevated plasma levels of IL‐17A‐associated cytokines were determined in an Asian cohort of infants with BA . Whether infiltration of the liver with Th17 lymphocytes and CD68 + iMΦ at the time of diagnosis is linked to progressive intrahepatic bile duct injury following KPE in North America will require further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Both T-cell [51,52] and B-cell-mediated autoimmunity [50,53] have been implicated as well as dysfunction of regulatory T-cells [54,55], activation of innate immunity and NK cells [56] and dendritic cells [57], activation of a pro-inflammatory gene footprint in liver tissue [58] and the loss of cholangiocyte primary cilia [59]. Recently, the contribution of interleukin-17 to the inflammation and destruction of the biliary system has been demonstrated, both in infants with BA and in the RRV newborn mouse model [60,61].…”
Section: Developments In Understanding Of the Pathogenesis Of Biliarymentioning
confidence: 99%
“…Analysis of human tissue reveals that high expression of IL-17 producing T cells was associated with need for liver transplant. Hill et al found high levels of Th17 cells in portal tracts of BA patients at diagnosis and the number of Th17 cells positively correlated with serum bilirubin levels, suggesting that IL-17 was directly responsible for bile duct injury [79]. …”
Section: T-cell Immunitymentioning
confidence: 99%